The behaviour and wellbeing of children and adults with severe intellectual disability and complex needs: the Be-Well checklist for carers and professionals. Issue 12 (December 2020) - Oliver, Chris; Adams, Dawn; Allen, Debbie; Crawford, Hayley; Heald, Mary; Moss, Jo; Richards, Caroline; Waite, Jane; Welham, Alice; Wilde, Lucy; Woodcock, Kate
Abstract: Children and adults with severe intellectual disability and complex needs often show behaviours and distress that carers and professionals find difficult to identify causes for, manage and decrease. The prevailing view is that these behaviours and distress are learned and consequently interventions focus on behavioural techniques. In this article we summarise the findings of research that indicate that behaviour and distress in this population are influenced by transient and stable characteristics or conditions that can interact with aspects of learning, be independent of learning, and interact with each other. These transient and stable characteristics or conditions are: pain and discomfort, sensory sensitivity, anxiety and low mood, sleep problems, atypical emotional regulation, specific cognitive difference, and differences in social behaviour. To aid carers and professionals, we present a checklist of the elements of an assessment process that covers these transient and stable characteristics or conditions and other relevant influences on behaviour and distress such as seizures, medication, learning and communication. We also draw attention to the benefit of identifying the cause of intellectual disability to inform the assessment process.